IMPLEMENTASI QUIZIZZ PADA PEMBELAJARAN SBdP MATERI UNSUR DAN PRINSIP SENI RUPA KELAS V SD NEGERI 011 SAMARINDA KOTA - Muhlis; Nur Aliyah; Usfandi Haryaka; Muh. Ramli Buhari; Sukriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study is driven by the usage of technology-based learning resources, such as Quizizz, that are beneficial to the field of education. More engaging and dynamic learning has been made possible with the Quizizz app, which also makes an intriguing assessment tool. This study aims to: (1) explain how SBdP learning was planned using Quizizz on the elements and principles of fine arts material; (2) explain how SBdP learning was implemented using Quizizz on the elements and principles of fine arts material; and (3) explain how SBdP learning was evaluated using Quizizz on the elements and principles of fine arts material. Descriptive study using a qualitative approach is the methodology used. Homeroom instructors and students from class V-A SDN 011 Samarinda City served as the study's subjects. The research included documentation, interviews, and observation as data collecting methods. Data gathering, data reduction, data presentation, and conclusion drawing were the methods of data analysis that were used. The following are the study's findings: (1) planning for arts and crafts learning using quizizz was carried out in class V-A by creating teaching modules, preparing teaching materials on quizizz media adjusted to learning resources, creating quiz questions on quizizz media and evaluation questions, preparing other learning support tools, (2) implementation of arts and crafts learning using quizizz was carried out one day in class, educators delivered teaching materials by displaying slides on quizizz, educators provided quiz codes to students to join the game, (3) evaluation of arts and crafts learning, educators provided formative assessments in the form of observations/observations of students' understanding, skills and attitudes during the implementation of learning using quizizz, then educators gave a written test consisting of 10 questions consisting of 5 multiple choice questions and 5 essay questions.